2020
DOI: 10.5056/jnm19208
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tight Junction Proteins According to Functional Dyspepsia Subtype and Sex

Abstract: Background/Aims To determine whether the expression of tight junction proteins (TJPs) differs depending on the subtype of functional dyspepsia (FD) and sex. Methods Control (n = 95) and FD (n = 165) groups based on Rome III criteria were prospectively enrolled. Gastric mucosal mRNA expression levels of various TJPs (claudins [CLDN] 1, 2, and 4; zonula occludens-1; occludin [OCLN]) were assessed by reverse transcription polymerase chain reaction. Western blot was performed to determine the levels of various TJP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Our team found that Helicobacter pylori was shown to be related to various tight junction proteins, particularly claudin-4 and occludin. 92 Interestingly, an increase in claudin-2 was thought to be involved in male functional dyspepsia but not in females. 92 …”
Section: Functional Gastrointestinal Disorder and Microbiome-gut-brain Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Our team found that Helicobacter pylori was shown to be related to various tight junction proteins, particularly claudin-4 and occludin. 92 Interestingly, an increase in claudin-2 was thought to be involved in male functional dyspepsia but not in females. 92 …”
Section: Functional Gastrointestinal Disorder and Microbiome-gut-brain Axismentioning
confidence: 99%
“… 92 Interestingly, an increase in claudin-2 was thought to be involved in male functional dyspepsia but not in females. 92 …”
Section: Functional Gastrointestinal Disorder and Microbiome-gut-brain Axismentioning
confidence: 99%
“…(42)(43)(44) We speculate these tight junction proteins might play to improve H. pylori-associated functional dyspepsia in addition to carcinogenesis. (45)(46)(47) Conclusively, since tight junction disruption is closely associated with either dysregulation of gastric mucosal barrier or gastric carcinogenesis, (48) kimchi afforded anticipating food factor to keep tight junction protein, CLDN18.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in susceptible conditions, a harmful pathogen or the consumption of certain foods impairs intestinal barrier function by altering tight junctions, resulting from proteasome‐mediated degradation triggered by inflammatory mediators including proteases, eicosanoids, and histamine 75 . Several studies showed that the expression of adhesion proteins, zonula occludens‐1 and occludin, was significantly lower in duodenal biopsy samples with decreased transepithelial resistance and impaired intestinal barrier function in FGID patients compared to controls 76,77 . Recently, a new endoscopic technology, confocal laser endomicroscopy and endocytoscopy, enables us to carry out a high‐resolution assessment of GI mucosal histology at cellular and subcellular levels and obtain “optical biopsies” of the endoluminal surface 78 .…”
Section: Pathophysiological Mechanisms Of Fgids With Special Emphasis On Gut Microbiota Dysbiosismentioning
confidence: 99%